Real and perceived swimming competency, risk estimation, and preventing drowning among New Zealand youth - Moran, K. (Biomechanics and Medicine in Swimming XI, 2010)
Little is known about youth swimming competency or of their perceptions of their risk of drowning. This study reports the New Zealand findings of an international project entitled the Can You Swim Project? The subjects (n = 68) were assessed in a two-part study using an initial questionnaire survey to provide self-estimates of swimming competency and risk perception, followed by a practical test of seven swimming competencies. Self-estimates of swimming compared well with actual measurements. Similar proportions were obtained for those who thought they could swim more than 300m (estimated 41%; actual 43%). No significant ender differences in real or perceived swimming competency were found. Significantly more males estimated lower risk of drowning associated with a series of aquatic scenarios. The implications of these findings on drowning prevention and the need for further investigation are discussed.